Vocation and altruism in nursing: The habits of practice - Carter, Melody (Nursing ethics, 2014)
Background:At a time when British nursing has been under scrutiny for an apparent lack of compassion in education and practice, this paper based offers a perspective on the notions of vocation and altruism in nursing.Objectives:To understand the vocational and altruistic motivations of nurses through the application of Pierre Bourdieu's concepts of ‘symbolic capital’, ‘field’ and ‘habitus’ through a long interview with nurse respondents.Research design:A reflexive qualitative study was undertaken using the long interview. A thematic analysis of the data, using a qualitative data software package for analysis, was undertaken. The ideas of Pierre Bourdieu (Habitus, Capital and Field) were used to analyse and explain the content of community nurses' ‘talk’.Participants:Twelve Community Nurses working in a variety of local primary care settings volunteered to participate in the study. It was a self-selecting convenience sample of nurses responding to an invitation to be interviewed.Research context:A study in support of a doctoral thesis conducted within NHS primary care settings with registered nurses.Ethical considerations:The key considerations for this study were to be mindful of the possibility of emotional harm or distress being caused to the respondents during the retelling of their experiences. It was also essential to ensure that the locations or names of patients or staff (if discussed) were anonymised. Ethical approval was sought and granted by both the Local NHS Primary Care and the University Ethics committees before the study commenced.Findings:The nurse respondents had highly individual and at times contradictory views on their motivations to nurse including their views on vocation and altruism in nursing careers.Discussion:Bourdieu's ideas apply well to the nursing context and provided a useful theoretical framework to explore the social and cultural influences on nursing careers. Gender is important consideration in all aspects of nursing but class and educational experience is an important dimension in the stories nurses tell.Conclusion:The culturally determined experiences of these nurses in practice offer an authentic and realistic insight into the complex motives and predispositions of community nurses. This paper argues that nurse motivations whether vocational or altruistic, are better understood as culturally, rather than spiritually, driven.